2017
DOI: 10.1186/s12993-017-0131-6
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral sensitivity of Japanese children with and without ADHD to changing reinforcer availability: an experimental study using signal detection methodology

Abstract: BackgroundMost research on motivational processes in attention deficit hyperactivity disorder (ADHD) has been undertaken in Western Europe and North America. The extent to which these findings apply to other cultural groups is unclear. The current study evaluated the behavioral sensitivity of Japanese children with and without ADHD to changing reward availability. Forty-one school-aged children, 19 diagnosed with DSM-IV ADHD, completed a signal-detection task in which correct discriminations between two stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Two recent response allocation studies (Alsop et al 2016;Furukawa et al 2017) used signal-detection methodology to evaluate the sensitivity of children with ADHD to changes in reward availability. Children with ADHD are known to experience difficulty adjusting their behavior according to situational demands (Douglas and Peters 1979;Barkley 1997) and this is reflected in current and previous diagnostic criteria (American Psychiatric Association 2013).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two recent response allocation studies (Alsop et al 2016;Furukawa et al 2017) used signal-detection methodology to evaluate the sensitivity of children with ADHD to changes in reward availability. Children with ADHD are known to experience difficulty adjusting their behavior according to situational demands (Douglas and Peters 1979;Barkley 1997) and this is reflected in current and previous diagnostic criteria (American Psychiatric Association 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Children with ADHD are known to experience difficulty adjusting their behavior according to situational demands (Douglas and Peters 1979;Barkley 1997) and this is reflected in current and previous diagnostic criteria (American Psychiatric Association 2013). Both Alsop et al (2016) and Furukawa et al (2017) reported the behavior of children with ADHD did not track the changing reinforcement contingencies as closely as their typically developing peers, when rates of reinforcement were low and there was uncertainty over the association between an action and its outcome. In the Alsop et al (2016) study, the ADHD group did alter their response allocation following the change in reinforcement contingencies, but to a smaller extent than was seen in the control group.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations